The comparative efficacy of FDA-approved drugs for management of alcohol use disorder ‒ a network meta-analysis - Kumar, Suresh; Shanmugham, Suresh; Tan, Fern Yee; Kong, Ashley Haze Zhi Xuan; Foong, Chen Xing; Chan, Jia En; Antony, Paul T.; Smales, Frederick Charles; Ching, Siew Mooi; Vadakkechalil, Harsha; Veettil, Sajesh K. (Rzeszów University Press, 2025)
Introduction and aim. Alcohol use disorder (AUD) represents a significant and lasting public health challenge affecting millions of people around the world. Currently, the US FDA has approved naltrexone, disulfiram, and acamprosate for AUD; however, their comparative effectiveness remains uncertain. This study aimed to evaluate the comparative efficacy of FDA-approved medications for AUD. Material and methods. A comprehensive search of PubMed, the Cochrane Library, and Embase was performed up to January 2025. Eligible studies were randomized controlled trials of at least 12 weeks in duration, enrolling adults with AUD and investigating one or more FDA-approved medications, individually or in combination. The Cochrane Risk of Bias 2 (ROB 2) tool was used to assess study quality. A frequentist random-effects network meta-analysis (NMA) was performed. The primary and secondary outcomes were the return to any level of drinking and the return to heavy drinking, respectively. Analysis of the literature. Fifty-two trials were included. Compared to placebo, acamprosate (risk ratio, RR, 0.87 [95% CI, 0.82-0.92]), naltrexone (0.93 [0.88-0.99]) and a combination of acamprosate and naltrexone (NAAC) (0.52 [0.35-0.76]) all statistically significantly reduced the risk of return to any type of drinking. Based on SUCRA rankings, NAAC (SUCRA = 0.99) was ranked first for efficacy. For the secondary outcome, only naltrexone (RR, 0.87 [0.80-0.95]) was found to be effective. Conclusion. When combined with psychosocial interventions, naltrexone and acamprosate demonstrated superior efficacy compared to placebo. Furthermore, the combination of the two medications led to significantly better results.
Keywords: acamprosate; alcohol use disorder; disulfiram; meta-analysis; naltrexone; randomized controlled trial